2002
DOI: 10.1068/c0225
|View full text |Cite
|
Sign up to set email alerts
|

Size and Political Trust: Evidence from Denmark, the Netherlands, Norway, and the United Kingdom

Abstract: This paper deals with two questions on the relations between the size of political systems and political trust. First, does citizens' trust in national elected officials differ from their trust in local elected officials? Second, what is the relationship between citizens' trust in elected local government officials and the size of local government units? These questions were answered on the basis of survey data from Denmark, the Netherlands, Norway and the United Kingdom. We found that trust in local officehol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 18 publications
(6 reference statements)
3
72
0
14
Order By: Relevance
“…9 In all of the other countries in this western European sample, local authorities are more trusted than national authorities. This confirms patterns observed in prior studies of the US, Japan, Norway, and the UK (Denters, 2002;Jennings, 1998;Pharr, 1997) that people tend to hold greater confidence in local governments than national governments. The size of the gap between trust in local authorities and national government also varies across countries, suggesting that there are important country-to-country differences in how people evaluate different levels of government.…”
Section: Levels Of Trust In Local and National Government In Western supporting
confidence: 91%
See 1 more Smart Citation
“…9 In all of the other countries in this western European sample, local authorities are more trusted than national authorities. This confirms patterns observed in prior studies of the US, Japan, Norway, and the UK (Denters, 2002;Jennings, 1998;Pharr, 1997) that people tend to hold greater confidence in local governments than national governments. The size of the gap between trust in local authorities and national government also varies across countries, suggesting that there are important country-to-country differences in how people evaluate different levels of government.…”
Section: Levels Of Trust In Local and National Government In Western supporting
confidence: 91%
“…Dahl and Tufte, 1973;Denters, 2002;Miller, 1988). We build on this work by considering the roots of public confidence in local government in western Europe.…”
Section: Introductionmentioning
confidence: 93%
“…However, there is no single or universal size effect. For example, when discussing size and political trust Denters (2002) points to six theoretical approaches suggesting different reasons why size matters. While for instance social trust based on strong personal ties is favoured in small municipalities, the strength of civic society is suggested to increase with size.…”
Section: Local Councillors and Democratic Legitimacymentioning
confidence: 98%
“…It is quite likely that the trust of political representatives is affected by the same factors as citizens’ trust. Social sciences have put a lot of effort into studying citizens’ political trust in institutions in all tiers of government (e.g., Denters ; Norén Bretzer ; Berg ; Aars & Christensen ; Kestilä‐Kekkonen & Söderlund ), and when citizens evaluate political institutions, it is often found that legitimacy based on procedures and performance is central to the generation of trust (e.g., Gustavsen et al ; Roos & Lidström ).…”
Section: Introductionmentioning
confidence: 99%